2019
DOI: 10.1186/s12974-019-1556-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 may produce damaging effect after cerebral ischemia by inducing astrocytes classical activation

Abstract: Background Functions of astrocytes in the rehabilitation after ischemic stroke, especially their impacts on inflammatory processes, remain controversial. This study uncovered two phenotypes of astrocytes, of which one was helpful, and the other harmful to anoxic neurons after brain ischemia. Methods We tested the levels of inflammatory factors including TNF-a, IL-6, IL-10, iNOS, IL-1beta, and CXCL10 in primary astrocytes at 0 h, 6 h, 12 h, 24 h, and 48 h after OGD, grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 43 publications
(52 reference statements)
3
60
0
Order By: Relevance
“…We also found that the ferritin and ceruloplasmin expressions in the hippocampi of KA-treated mice were reduced by LCN2 deletion. Nitric oxide, produced by iNOS, is known to cause neuronal damage and apoptotic cell death after KA administration [ 50 ], and LCN2 has been shown to produce a damaging effect after cerebral ischemia by inducing high iNOS expression in astrocytes both in vivo and in vitro [ 51 ]. Consistently, we found that iNOS expression increased in a time-dependent manner in KA-treated WT mice, but remained at baseline in LCN2 (−/−) mice.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the ferritin and ceruloplasmin expressions in the hippocampi of KA-treated mice were reduced by LCN2 deletion. Nitric oxide, produced by iNOS, is known to cause neuronal damage and apoptotic cell death after KA administration [ 50 ], and LCN2 has been shown to produce a damaging effect after cerebral ischemia by inducing high iNOS expression in astrocytes both in vivo and in vitro [ 51 ]. Consistently, we found that iNOS expression increased in a time-dependent manner in KA-treated WT mice, but remained at baseline in LCN2 (−/−) mice.…”
Section: Discussionmentioning
confidence: 99%
“…A neurological behavior assessment was made according to previous methods 24 h after reperfusion. By mNSS scoring standards 20 , mild injury is scored 0 to 6 points, moderate injury 7 to 12 points, and severe injury 13 to 18 points. The mNSS score assessed was 18 points.…”
Section: Evaluation Of Neurologic De Citsmentioning
confidence: 99%
“…Consistent with these studies, we found that the levels of LCN2 increase dramatically in the stroked brain. Since both NE and LCN2 have been shown to mediate neuroinflammation and BBB damage in stroke (64)(65)(66)(67)(68), reduced levels of NE and LCN2 in COX-2 deficient animals could be a potential mechanism underlying the vasculoprotective effects of COX-2 blockade in stroke.…”
Section: Discussionmentioning
confidence: 99%